2017
DOI: 10.1093/mnras/stx785
|View full text |Cite
|
Sign up to set email alerts
|

On the linearity of tracer bias around voids

Abstract: The large-scale structure of the universe can only be observed via luminous tracers of the dark matter. However, the clustering statistics of tracers are biased and depend on various properties, such as their host-halo mass and assembly history. On very large scales this tracer bias results in a constant offset in the clustering amplitude, known as linear bias. Towards smaller non-linear scales, this is no longer the case and tracer bias becomes a complicated function of scale and time. We focus on tracer bias… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
97
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(119 citation statements)
references
References 119 publications
(169 reference statements)
22
97
0
Order By: Relevance
“…Given the high level of uncertainty in the inner regions of the profiles, due to the sparsity of tracers, we exclude all the values with r ≤ 0.5 r eff . In agreement with the results by Pollina et al (2017), we find that the densities measured with the two different tracers, that is DM particles and haloes, are linearly related:…”
Section: Biased Tracerssupporting
confidence: 91%
See 1 more Smart Citation
“…Given the high level of uncertainty in the inner regions of the profiles, due to the sparsity of tracers, we exclude all the values with r ≤ 0.5 r eff . In agreement with the results by Pollina et al (2017), we find that the densities measured with the two different tracers, that is DM particles and haloes, are linearly related:…”
Section: Biased Tracerssupporting
confidence: 91%
“…Given the hypothesis that voids in tracers are centred in the same position of their DM counterparts, we search for the density contrast that voids identified in the tracer distribution reach in the underlying DM distribution. By taking the ratio between the two profiles, as suggested by Pollina et al (2017), one can infer the relation between the density measured from biased tracers and the underlying unbiased DM density. Figure 4 shows the ratio between all the stacked profiles obtained for each catalogue, markers with error bars representing the uncertainty on the mean in the bin.…”
Section: Biased Tracersmentioning
confidence: 99%
“…• The theoretical void size function is referred to the statistical properties of matter, not of the tracers. We follow Pollina et al [20,66] to compute the threshold in the matter δ m v,NL , which corresponds to the one in the halo distribution and then invert the linear bias relation δ H v,NL = b eff × δ m v,NL (with b eff being the tracer bias). • In order to calculate the theoretical void size function, we need to express the matter underdensity threshold in linear theory.…”
Section: Void Catalogue Preparationmentioning
confidence: 99%
“…To overcome this issue, we implemented a simpler method to embed the bias dependency in the underdensity threshold value. Pollina et al (2017) found that the relation between the non-linear density contrast of tracers, δ NL v, tr , and matter, δ NL v, DM , around voids is linear and determined by a multiplicative constant which corresponds to the value of the bias parameter of the tracer sample, b:…”
Section: The Size Function Of Cosmic Voids In the Distribution Of Biamentioning
confidence: 99%